2001
DOI: 10.1645/0022-3395(2001)087[1498:hpitpo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hunting Practices Increase the Prevalence ofTrichinellaInfection in Wolves From European Russia

Abstract: From 1998 to 2000, 184 animals (82 wolves, 29 red foxes, 55 mustelids, 5 raccoon dogs, and 13 domestic dogs), mainly shot by hunters in the Tvier and Smoliensk regions of northwest European Russia, were tested for Trichinella larvae; 98 animals (53.3%) were found to be positive. The highest prevalence was detected in wolf (97.5%). Trichinella nativa was the most common species detected (98%). The diet of wolves was investigated by examining the stomach contents of 62 animals (75.6% of the total number of wolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Since the prevalence of Trichinella spp. in Polish red foxes is high (10%) (Cybulska et al, 2016), leaving the skinned carcasses of foxes and other carnivores after a hunt in the forest creates a risk factor for spreading of Trichinella infections to both wild rodents and other susceptible wild animals (Pozio et al, 2001). Furthermore, cannibalism is well recorded among rodent species (Reperant and Deplazes, 2005), especially in association with aggressive behavior (Marchlewska-Koj et al, 1989) linked to dominance hierarchies (Gustafsson et al, 1980), protection of nests and competition for mates (Horne and Ylönen, 1996; Marchlewska-Koj et al, 1989; Ylönen and Horne, 2002) and this may contribute also to dissemination of Trichinella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Since the prevalence of Trichinella spp. in Polish red foxes is high (10%) (Cybulska et al, 2016), leaving the skinned carcasses of foxes and other carnivores after a hunt in the forest creates a risk factor for spreading of Trichinella infections to both wild rodents and other susceptible wild animals (Pozio et al, 2001). Furthermore, cannibalism is well recorded among rodent species (Reperant and Deplazes, 2005), especially in association with aggressive behavior (Marchlewska-Koj et al, 1989) linked to dominance hierarchies (Gustafsson et al, 1980), protection of nests and competition for mates (Horne and Ylönen, 1996; Marchlewska-Koj et al, 1989; Ylönen and Horne, 2002) and this may contribute also to dissemination of Trichinella spp.…”
Section: Discussionmentioning
confidence: 99%
“…the ecological niche of the larvae of Trichinella spp. In many areas of the world where hunting is practiced, hunting dogs have easy access to muscle samples of game including carnivore carcasses (e.g., foxes, mustelids, bears, walruses), left on the ground by hunters after skinning, or removing and discarding the entrails [ 41 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies however, stated the number of single larvae tested per host animal, or the success rate. One study by Pozio et al [ 30 ] on wildlife samples frozen at −20 and −80 °C, used 5 to 10-fold single larva multiplex PCRs to identify the Trichinella species, but did not mention how many of these larvae actually were identified. The use of multiple attempts in that study implicated that it was at least anticipated to have a low success rate.…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of 29% in foxes in Latvia. In that publication, individual larvae were identified with PCR according to Pozio et al [ 30 ], which showed a distribution of 78% T. britovi , 8.5% T. nativa and 9.3% mixed infection of the two species in 129 Latvian foxes. Although our sample size of Latvian foxes is much lower and primarily aimed at the validation of our method, we found a comparable distribution of T. britovi and T. nativa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation